A STUDY ABOUT ONLINE GAME ADDICTION AMONG STUDENTS OF STATE SENIOR HIGH SCHOOL 6 PADANGSIDIMPUAN CITY - Efrida Dalimunthe; Muhammad Ihsan (Madiha Press, 2025)
The rapid development of knowledge and technology has had more impact on people’s lives recently. The research location was at SMA Negeri 6 (Senior High School) Padangsidimpuan City. The population used in this study was all students of SMA Negeri 6 (Senior High School) Padangsidimpuan City. Online Game addiction is categorized as a very high category and there are 49 students with a percentage of 47.57%. Then, 6 students are in a high category with the percentage of 5.83%, 7 students are in a moderate category with the percentage of 6.80%. Moreover, there are 25 students in a low category with a percentage of 24.27%, and there are 16 students in a very low category with a percentage of 15.53%. The online game addiction aspects used are; the average score of salience obtained is 16.38 with a percentage of 65.52%. The aspect of tolerance is 16.43 or equivalent to 65.72%, the aspect of mood modification is in an average of 15.94 or equivalent to 63.76%. In addition, the average score on the aspect of repetition or relapse is 16.02 or equivalent to 64.08%, the average score on the withdrawal aspect is 16.82 or equivalent to 67.28%, and the average score on the conflict aspect is 15.91 or equivalent to 63.64%. Finally, the average score of problem aspect is 16.53 or equivalent to 66.12%.